2020
DOI: 10.1093/biosci/biaa039
|View full text |Cite
|
Sign up to set email alerts
|

Connected Carabids: Network Interactions and Their Impact on Biocontrol by Carabid Beetles

Abstract: Carabid beetles can greatly contribute to biocontrol in agroecosystems, reducing both insect pests and weed seeds. However, insect foraging and feeding behavior can be highly dependent on the interaction network and spatial structure of the environment, which can make their biocontrol contributions variable. In the present article, we explore how the interaction network of carabids can affect their behavior and how spatial vegetation structure and specific agronomy practices can, in turn, affect the strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 93 publications
1
36
0
Order By: Relevance
“…In conclusion, the combination of alley cropping and organic farming should be the best option for enhancing both weed seed and invertebrate pest control, provided that niche complementarity outweighs intraguild predation (Straub et al, 2008;Heij and Willenborg, 2020). Our results are in line with those of Caro et al (2016) and Fusser et al (2018), who found that AEI had stronger effect on carabid diversity when combined with organic farming.…”
Section: Positive Effects Of Alley Cropping Agroforestry On Generalissupporting
confidence: 87%
See 1 more Smart Citation
“…In conclusion, the combination of alley cropping and organic farming should be the best option for enhancing both weed seed and invertebrate pest control, provided that niche complementarity outweighs intraguild predation (Straub et al, 2008;Heij and Willenborg, 2020). Our results are in line with those of Caro et al (2016) and Fusser et al (2018), who found that AEI had stronger effect on carabid diversity when combined with organic farming.…”
Section: Positive Effects Of Alley Cropping Agroforestry On Generalissupporting
confidence: 87%
“…Organic farming also favors the presence of a rich and abundant weed flora, which provides additional habitats and trophic resources such as seeds and pollen, but also phytophagous prey (Batáry et al, 2012). Alternative food is important both to sustain predators when pest populations are low and to mitigate intraguild predation, although it can also distract predators from main crop pests (Heij and Willenborg, 2020). It has been shown that organic farming increases the abundance and species richness of carabid communities (Djoudi et al, 2019), especially by favoring predominantly granivorous carabid species and those with a large body length (Diekötter et al, 2016;Gallé et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily to chrysopids and mirid bugs, the use of carabid beetles as BCAs for insect pests has not been suggested. Carabids are generalist predators, feeding on insect pests but also weed seeds, which decreases consumption rates of one or the other [ 49 ]. Still, Carabidae species were already reported as predators of pests such as Ragholetis mendax Curran (blueberry fruit fly) [ 50 ], Itame argillacearia Packard (blueberry spanworm), Altica sylvia Malloch (blueberry flea beetle) [ 51 ] or Acalymma vittatum (Fabricius) (striped cucumber beetle) [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was valuable to develop this method for carabid beetles because they are mobile predators of invertebrate pests and weed seeds in arable crops. In particular they are known to contribute to weed seed regulation in agro-ecosystems (Bohan, Boursault, et al, 2011;Honek et al, 2003;Kulkarni, Dosdall, & Willenborg, 2015), and network approaches have been recommended to study the direct and indirect effects of carabid biocontrol (De Heij & Willenborg, 2020). The key novelty of our approach, compared to other approaches (Morales-Castilla et al, 2015) is that we estimated interaction strength, scaled up from per capita estimates of interactions.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that the network model we have developed could, with care, be extended to include invertebrates as an alternate prey if the risk index could be estimated for invertebrates as well as seed prey (Roubinet et al, 2018). This would provide a powerful framework for predicting biocontrol across the community of granivorous and omnivorous carabids (De Heij & Willenborg, 2020; Ma et al, 2019).…”
Section: Discussionmentioning
confidence: 99%